2016
DOI: 10.3389/fpls.2016.00207
|View full text |Cite
|
Sign up to set email alerts
|

Vernalization Requirement and the Chromosomal VRN1-Region can Affect Freezing Tolerance and Expression of Cold-Regulated Genes in Festuca pratensis

Abstract: Plants adapted to cold winters go through annual cycles of gain followed by loss of freezing tolerance (cold acclimation and deacclimation). Warm spells during winter and early spring can cause deacclimation, and if temperatures drop, freezing damage may occur. Many plants are vernalized during winter, a process making them competent to flower in the following summer. In winter cereals, a coincidence in the timing of vernalization saturation, deacclimation, downregulation of cold-induced genes, and reduced abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 71 publications
(83 reference statements)
1
10
0
Order By: Relevance
“…Oliver et al [107] therefore suggested that VRN1 and COR14B may be regulated by similar mechanisms in early cold acclimation, possibly through the action of CBF transcription factors. Several studies show that CBF6 and COR14B are down-regulated in cereals and meadow fescue by prolonged cold, but only under long photoperiods [105]. Taken together, these results suggest that VRN1 and the CBF regulon are co-regulated during cold acclimation of temperate grasses and as long as photoperiods are short, but that VRN1 down-regulates CBFs when photoperiods become long (Figure 3).…”
Section: Regulation Of Leaf Growth Versus Freezing Resistance In Springsupporting
confidence: 58%
See 4 more Smart Citations
“…Oliver et al [107] therefore suggested that VRN1 and COR14B may be regulated by similar mechanisms in early cold acclimation, possibly through the action of CBF transcription factors. Several studies show that CBF6 and COR14B are down-regulated in cereals and meadow fescue by prolonged cold, but only under long photoperiods [105]. Taken together, these results suggest that VRN1 and the CBF regulon are co-regulated during cold acclimation of temperate grasses and as long as photoperiods are short, but that VRN1 down-regulates CBFs when photoperiods become long (Figure 3).…”
Section: Regulation Of Leaf Growth Versus Freezing Resistance In Springsupporting
confidence: 58%
“…For example, carbohydrates did not accumulate to the same extent during re-acclimation as during initial cold acclimation in winter wheat [114], and several cold induced genes upregulated by cold acclimation in meadow fescue were not upregulated during re-acclimation [105]. The mechanisms behind these differences are not known, but are likely to be related to a coordinated regulation of growth and freezing tolerance as described in Section 2.3.…”
Section: Is Re-acclimation In Spring Different From Cold Acclimation mentioning
confidence: 92%
See 3 more Smart Citations